2013
DOI: 10.1128/mbio.00105-13
|View full text |Cite|
|
Sign up to set email alerts
|

Aromatic Amino Acids Required for Pili Conductivity and Long-Range Extracellular Electron Transport in Geobacter sulfurreducens

Abstract: It has been proposed that Geobacter sulfurreducens requires conductive pili for long-range electron transport to Fe(III) oxides and for high-density current production in microbial fuel cells. In order to investigate this further, we constructed a strain of G. sulfurreducens, designated Aro-5, which produced pili with diminished conductivity. This was accomplished by modifying the amino acid sequence of PilA, the structural pilin protein. An alanine was substituted for each of the five aromatic amino acids in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
204
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(223 citation statements)
references
References 35 publications
18
204
0
1
Order By: Relevance
“…Until recently, it was assumed that the type IV pili were important for S. oneidensis nanowire formation and function, similar to the nanowires described in Geobacter sulfurreducens (6,7). We previously demonstrated that pili are not required for the formation of S. oneidensis MR-1 nanowires.…”
mentioning
confidence: 99%
“…Until recently, it was assumed that the type IV pili were important for S. oneidensis nanowire formation and function, similar to the nanowires described in Geobacter sulfurreducens (6,7). We previously demonstrated that pili are not required for the formation of S. oneidensis MR-1 nanowires.…”
mentioning
confidence: 99%
“…However, the terminal electron transfer in DL-1 appears to take place through electrically conductive pili (23,24). The pili have homology to the type IV pili of other Gram-negative bacteria, but PilA, the structural pilin protein, is truncated compared to the PilA of other well-studied organisms, such as Pseudomonas aeruginosa, whose pili do not appear to be conductive (25). Deletion of pilA prevents Fe(III) oxide reduction in DL-1, but the mutant can be rescued with the addition of an electron shuttle or Fe(III) chelator, demonstrating that the pili are specifically required for Fe(III) oxide reduction (26).…”
mentioning
confidence: 99%
“…Deletion of pilA prevents Fe(III) oxide reduction in DL-1, but the mutant can be rescued with the addition of an electron shuttle or Fe(III) chelator, demonstrating that the pili are specifically required for Fe(III) oxide reduction (26). Electrons move along the pili through a metallic-like conduction (27,28) that can be attributed to overlapping pi-pi orbitals of aromatic amino acids in the carboxyl terminus of PilA (25). The multiheme c-type cytochrome OmcS (21,29) is associated with the pili (30) and is essential for Fe(III) oxide reduction, presumably facilitating electron transfer from the pili to the Fe(III) oxides (23,24).…”
mentioning
confidence: 99%
“…Geobacter sulfurreducens, and presumably other Geobacter species, produce electrically conductive pili that have been proposed to serve as a conduit for extracellular electron transfer (2,3), but the mechanisms for electron transfer along G. sulfurreducens pili is a matter of considerable debate (4)(5)(6). Laboratories that have experimentally investigated G. sulfurreducens pili have concluded that electron transport along the pili is an intrinsic function of the pili itself and does not involve electron hopping/tunneling between traditional electron transfer proteins, such as cytochromes (2,3,7,8), even though the c-type cytochrome OmcS is associated with the pili (9,10). This contrasts to the proposed cytochrome-to-cytochrome electron hopping/tunneling along conductive filaments of Shewanella oneidensis (11,12).…”
mentioning
confidence: 99%